2008
DOI: 10.1007/s00024-008-0365-1
|View full text |Cite
|
Sign up to set email alerts
|

Body-wave Attenuation in the Region of Garda, Italy

Abstract: We analyzed the spectral amplitude decay with hypocentral distance of P and S waves generated by 76 small magnitude earthquakes (M L 0.9-3.8) located in the Garda region, Central-Eastern Alps, Italy. These events were recorded by 18 stations with velocity sensors, in a distance range between 8 and 120 km. We calculated nonparametric attenuation functions (NAF) and estimated the quality factor Q of both body waves at 17 different frequencies between 2 and 25 Hz. Assuming a homogeneous model we found that the Q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…There are several studies for various regions of the world that have considered Q S /Q P , and most of them report the ratio Q S /Q P >1 for all frequencies. Castro et al (2008) found Q S /Q P to be between 0.7 and 2.8 for the region of Garda, the Central Alps, which is in an excellent agreement with results presented here. Yoshimoto et al (1993) estimated Q S /Q P >1 for Kanto region, Japan, whereas Mahood et al (2009) obtained ratios between 1.3 and 2.0 in East Central Iran.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There are several studies for various regions of the world that have considered Q S /Q P , and most of them report the ratio Q S /Q P >1 for all frequencies. Castro et al (2008) found Q S /Q P to be between 0.7 and 2.8 for the region of Garda, the Central Alps, which is in an excellent agreement with results presented here. Yoshimoto et al (1993) estimated Q S /Q P >1 for Kanto region, Japan, whereas Mahood et al (2009) obtained ratios between 1.3 and 2.0 in East Central Iran.…”
Section: Resultssupporting
confidence: 93%
“…1)et al (1996) estimated Q S =16f 0.92 from accelerograms for the Friuli region in NE Italy. For the region of Garda,Castro et al (2008) reported Q P =65f 0.9 and Q S =160f 0.6…”
mentioning
confidence: 96%
“…The considered source-to-station distances (mostly within 35 km) are on average shorter than the usual range of GIT applications (e.g., Castro et al, 2008;Bindi et al, 2009), and the inter-station distance is, in some cases, smaller than 1 km. Under such condition of short and similar ray paths, the method could fail in separating simultaneously the effect of site, source, and attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…We work on almost 16000 waveforms from 770 earthquakes recorded by 54 stations. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 23 Figure 5 -Comparison of our <Q> for coda and direct waves obtained for the whole Northern Italy with some regional relationships for the Western Alps (Morasca et al 2006, Walter et al 2007 for station BNI), Eastern Alps (Castro et al 1996;Console and Rovelli, 1981;Malagnini et al 2002;Walter et al 2007 for station TRI) Central Alps , Castro et al 2008) and Apennines (Malagnini et al 2000).…”
Section: Discussionmentioning
confidence: 91%
“…Within Northern Italy, the Q parameter has been defined using one-dimensional models for different sub-regions (e.g., Morasca et al 2006 and, for the Western Alps; Thouvenot, 1983, Castro et al 2008 for the Central Alps; Malagnini et al 2002, Castro et al 1996and Console and Rovelli, 1981 for the Eastern Alps). The motivation for improving upon the 2-D attenuation model for Northern Italy is several fold.…”
Section: Introductionmentioning
confidence: 99%